The Dark Side of Top Level Sport: An Autobiographic Study of Depressive Experiences in Elite Sport Performers - Newman, Hannah J. H.; Howells, Karen L.; Fletcher, David (Frontiers in Psychology, 2016)
The general and sport psychology research converge to point to a complex relationship between depressive experiences and human performance. The purpose of this study was to explore the depressive experiences of top level athletes and the relationship of such experiences with sport performance. Twelve autobiographies of elite athletes representing eight sports were analyzed. The autobiographical analysis was informed by narrative tradition, using three types of narrative analysis: categorical content, categorical form, and holistic content. The analysis revealed a temporal aspect to the depressive experiences that the athletes reported. Initially, sport represented a form of escape from the depressive symptoms which had been exacerbated by both external stressors (e.g., experiencing bereavement) and internal stressors (e.g., low self-esteem). However, in time, the athletes typically reached a stage when the demands of their sport shifted from being facilitative to being debilitative in nature with an intensification of their depressive symptoms. This was accompanied by deliberations about continuing their engagement in sport and an acceptance that they could no longer escape from their symptoms, with or without sport. The findings extend the extant literature by suggesting a reciprocal relationship between depressive experiences and sport performance, and they support the general psychology literature relating to the negative impact of depression on performance. The applied implications of these findings are discussed emphasizing the importance of early identification of depressive symptoms and the adoption of a proactive approach in the prevention and management of symptoms.